Breg Cells Are Numerically Decreased and Functionally Impaired in Patients With Systemic Sclerosis - Mavropoulos, Athanasios; Simopoulou, Theodora; Varna, Areti; Liaskos, Christos; Katsiari, Christina G.; Bogdanos, Dimitrios P.; Sakkas, Lazaros I. (Arthritis & rheumatology (Hoboken, N.J.), 2016)
Objective Breg cells, a regulatory cell subset that produces interleukin‐10 (IL‐10), play a significant role in suppressing autoimmune responses and preventing autoimmunity. This study was undertaken to examine the number and function of Breg cells in patients with systemic sclerosis (SSc), a disease with many autoantibodies. Methods Forty‐five patients with SSc (12 with early SSc, 33 with established disease including 16 with SSc‐associated pulmonary fibrosis [PF]), 12 healthy control subjects, and 10 patients with rheumatoid arthritis (RA)–associated PF were studied. The phenotypes of immature/transitional Breg cells (CD19+CD24highCD38high) and memory Breg cells (CD19+CD27+CD24high) were evaluated by flow cytometry. The function of Breg cells was assessed by measuring the production of IL‐10 after B cell activation. In addition, activation of p38 MAPK and STAT‐3 was measured following stimulation of the cells with B cell receptor (BCR) and Toll‐like receptor 9 (TLR‐9). Results Percentages of memory Breg cells were decreased in patients with early SSc (mean ± SEM 1.85 ± 0.38%), those with established SSc (1.6 ± 0.88%), those with SSc‐associated PF (1.52 ± 0.17%), and those with RA‐associated PF (1.58 ± 0.26%), compared to healthy controls (6.3 ± 0.49%; each P < 0.001). Percentages of transitional Breg cells were also decreased. Expression of IL‐10 by Breg cells after stimulation with TLR‐9 was impaired in patients with SSc, particularly those with SSc‐associated PF. Activation of STAT‐3 and p38 MAPK was impaired in naive and memory B cells from patients with SSc after stimulation with BCR and TLR‐9. Expression of the stimulatory CD19 receptor was increased in B cells and also increased, to a lesser extent, in Breg cells from patients with SSc compared to healthy controls. Percentages of memory B cells were decreased in patients with SSc, particularly in those with SSc‐associated PF. Conclusion This is the first study to demonstrate that Breg cells are phenotypically and functionally impaired in patients with SSc. Furthermore, in SSc, B cells exhibit impaired p38 MAPK and STAT‐3 activation upon stimulation with BCR and TLR‐9. The findings of decreased numbers of Breg cells along with increased expression of CD19 support the idea of B cell autoaggression acting as an immunopathogenic mediator in SSc.